1992
DOI: 10.1159/000186709
|View full text |Cite
|
Sign up to set email alerts
|

Intraglomerular Proteinase Activity in Adriamycin-lnduced Nephropathy

Abstract: Adriamycin (ADR)-induced nephropathy is characterized by focal and segmental glomerulosclerosis and is supposed to be an ideal model of chronic progressive renal disease. The aim of our study was to investigate whether there might be an altered activity of glomerular proteinases in ADR nephropathy, thereby aggravating glomerular protein accumulation as an important initiating hallmark of glomerulosclerosis. In fact, we could demonstrate significantly enhanced levels of intraglomerular protein and DNA content i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 15 publications
1
9
1
2
Order By: Relevance
“…In accordance with the suggestion of an ADR-impaired proteolytic degradation, glomerular protein accumulation has recently also been assigned to a diminished proteolytic activity in glomeruli of ADRtreated rats [3]. ADR, either directly or me diated by reactive oxygen species, interferes with proteolytic activities by both changing the substrate protein or the enzyme itself.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In accordance with the suggestion of an ADR-impaired proteolytic degradation, glomerular protein accumulation has recently also been assigned to a diminished proteolytic activity in glomeruli of ADRtreated rats [3]. ADR, either directly or me diated by reactive oxygen species, interferes with proteolytic activities by both changing the substrate protein or the enzyme itself.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies proved that alterations in the glomerular metabolic balance, such as in creased protein synthesis [1,2] and/or dimin ished proteolytic activities [3,4] with a con comitant enrichment of protein into the glo merulus, play an important role during the development of glomerulopathies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed mechanisms of ADR-induced tissue damage include introduction of double-stranded DNA breaks (DSBs), lipid peroxidation, inhibition of protease activity, disruption of the cytoskeletal and extracellular matrix, and inhibition of the topoisomerase II-mediated religation of the broken DNA strands (13)(14)(15)(16). In addition, mutations in mitochondrial DNA (mtDNA) and reduction in mtDNA copy number have been increasingly identified as major contributors to ADR-induced tissue injury: ADR can damage mtDNA directly, by intercalating into mtDNA, or indirectly, by generating ROS, producing mtDNA depletion in the kidney and heart after short-term treatment (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that there may be defective collagenolytic activity in injured glomeruli that progress to glomerulosclerosis, with a resulting imbalance between synthesis and degradation [144]. Glomeruli from Adriamycin-induced nephropathy have been shown to have decreased collagenolytic activity [153, 154]; although cultured mesangial cells from transgenic mice overexpressing growth hormone have decreased matrix metalloproteinase 9 levels, remnant glomeruli have increases in matrix metalloproteinase 2 and TIMP-1 and TIMP-2 [155], suggesting complex interactions mediating the net decreases in collagenolytic activity.…”
Section: Responses To Injurymentioning
confidence: 99%